Deep stabilization muscles training in patients with polyarticular hypermobility - Gębska, Magdalena; Weber-Nowakowska, Katarzyna; Żółtowska, Oliwia; Żyżniewska-Banaszak, Ewelina; Woitas-Ślubowska, Donata (Journal of Education, Health and Sport, 2017)
Hypermobility syndrome is an inherited dysfunction in the structure of connective tissues. It is manifested by disturbances in the proportion of collagen. The main symptoms of this syndrome are: laxity joint capsules and ligaments, range Increasing the mobility of joints, pain and many disorders and Functioning of organs and systems containing connective tissue. Improperly selected and dosed physical effort in patients with hypermobility syndrome can lead a frequent injuries and overload the musculoskeletal system. The consequence will be early degenerative changes and disability.